EFISIENSI METODE ECONOMICAL ORDER QUANTITY (EOQ) DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN BAHAN BAKU DAN PENGARUHNYA TERHADAP TOTAL BIAYA PEMBELIAN PADA PT AMITEX (AMANAH MITRA INDUSTRI) BUARAN KABUPATEN PEKALONGAN - Prihasdi, Rahardyan Dwa; Rahardjo, Shiddiq Nur (Diponegoro Journal of Accounting, 2012)
This research has purpose to compare traditional counting way with Economical Order Quantity (EOQ) method in decision making on basic material buying . This research object is decision making on material buying PT Amitex Buaran Pekalongan regency from 2008 to 2010. PT Amitex is standart export palekat sarung producer. Datas which used in this research are interview, documentation and study library. The analysis data uses descriptive technique analysis and nonstatistic quantitative with analysis instrument of order cost, saving cost, Economical Order Quantity (EOQ) method, which include frequency, amount, and the total cost of basic material buying, safety stock, and reorder point. The out come of this research show that the EOQ method more efficient in decision making on basic material buying than traditional counting way and the EOQ method have positive effect to total cost of basic material buying. By the EOQ method, the company advantage in creasing because there is efficient total buying cost are Rp 578.759.820,00 or 48,691 % in 2008, Rp 807.911.950,00 or 60,277% in 2009, and Rp 1.046.754.432,00 or 60,277% in 2010